TINJAUAN HUKUM PIDANA TERHADAP TINDAK PIDANA KORUPSI DALAM MASYARAKAT (Review of Criminal Law on Corruption in Society) - Hutabarat, Dany Try Hutama; Napitupulu, Celly Naumi Sarah Br.; Adila, Lica; Siagian, Angela Ekklesia; Manik, Susih Gajah; Malau, Rado; Sirait, Deviana Dewi; Mangunsong, Juliana; Harmika, Zuwairiah; Sahera, Miri (Nusantara Hasana Berdikari, 2022)
This mini research is the result of normative research that aims to answer the formulation of the problem regarding the review of criminal law against corruption in society. The research method used is a method with a normative approach, namely an approach based on the main legal material by examining theories, concepts, legal principles and legislation related to this research. Corruption is like something that has been ingrained in our society. Corruption is not only detrimental to state money, but also robs the state of rights and the state's economy. In this case the relevant agencies must play an active and creative role in handling this case and also involve the community in it.